Method and verification of strength determination for dense filling coal mining filling body in comprehensive mechanized unit - Pengliang LIU; Xiaoqing WANG (Meitan kexue jishu)
The comprehensive mechanized unit dense filling coal mining technology combines the functions of rock movement control and solid waste disposal, and has advantages such as parallel mining and filling, flexible process, and low investment. The reasonable design of filling body strength is related to bearing effect and economic benefits, but there is still a lack of targeted scientific basis. Taking three rounds of mining and filling as an example, theoretical analysis shows that the comprehensive mechanized unit dense filling coal mining face presents a “coal pillar filling body” phased transfer bearing characteristic, which can be divided into three stages: “coal pillar comprehensive bearing”, “filling body participating in bearing”, and “filling body comprehensive bearing”. Based on the Rankine earth pressure theory, the calculation formula for the lateral pressure of the filling body in the three directions of the support roadway is obtained; The relationship between the elastic modulus of the filling material and the maximum horizontal deformation of the surface was derived and established based on the equivalent mining height and the calculation formula for surface horizontal deformation; The laboratory experiment obtained the elastic modulus of 9 sets of paste specimens with uniaxial compressive strength of 1-5 MPa under triaxial confining pressures of 0, 0.5, 1.0, and 1.5 MPa, respectively. The relationship between the uniaxial compressive strength of the filling material and the elastic modulus under triaxial conditions was established. Thus, a calculation formula for the uniaxial compressive strength of the filling material based on the surface horizontal deformation index was established. A numerical model was established based on the first mining face of the 51106 shallow buried and thick coal seam in a certain mine. The study showed that the vertical stress curve above the “coal pillar filling body” of the working face showed a steep wave like distribution after the first two rounds of mining and filling, with slight surface subsidence and horizontal deformation. After the third round of mining and filling, the stress curve showed a gentle wave like shape, with a significant increase in surface subsidence and horizontal deformation. This verified the characteristic of the “coal pillar filling body” transfer bearing in stages. At the same time, numerical simulation and engineering practice showed that the method for determining the uniaxial compressive strength of the filling body is reasonable and accurate, which can provide reference for the strength design of the filling body of the comprehensive mechanized unit dense filling coal mining working face.